Telecommunication network economics from theory to applications - Maillé, Patrick (Cambridge University Press, 2014)
Presenting a balance of theory and practice, this up-to-date guide provides a comprehensive overview of the key issues in telecommunication network economics, as well as the mathematical models behind the solutions. These mathematical foundations enable the reader to understand the economic issues arising at this pivotal time in network economics, from business, research and political perspectives. This is followed by a unique practical guide to current topics, including app stores, volume-based pricing, auctions for advertisements, search engine business models, the network neutrality debate, the relationship between mobile operators and mobile virtual network operators, and the economics of security. The guide discusses all types of players in telecommunications, from users, to access and transit network providers, to service providers (including search engines, cloud providers or content delivery networks), to content providers and regulatory bodies. Ideal for graduate students, researchers and industry practitioners working in telecommunications